Helping smallholder farmers mitigate climate change - Wollenberg, Eva Karoline; Higman S; Seeberg-Elverfeldt, C; Neely, Constance; Tapio-Bistrom, M.L.; Neufeldt, Henry (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
Key messages - Smallholder farmers can contribute significantly to climate change mitigation but will need incentives to adapt their practices. - Incentives from selling carbon credits are limited by low returns to farmers, high transaction costs, and the need for farmers to invest in mitigation activities long before they receive payments. - Improved food security, economic benefits and adaptation to climate change are more fundamental incentives that should accompany mitigation. - Designing agricultural investment and policy to provide up-front finance and longer term rewards for mitigation practices will help reach larger numbers of farmers than specialized mitigation interventions.